Ketetapan MPR Dalam Tata Urutan Peraturan Perundang-undangan Di Indonesia - Sati, Nisrina Irbah (UI Scholars Hub, 2019)
As a result of deliberation and representation based democracy in Indonesia, the UUD 1945 before the amendment presented MPR as the highest state institution that absorbed people's sovereignty, so it gained legitimacy to be a superordinate of state institutions in various branches of power. The MPR’s position as the highest state institution was also accompanied by a legislative function, in which the MPR was able to make its legal product known as Tap MPR. The change in the position of the MPR, which was no longer the highest institution of the state in the constitutional structure since the enactment of The 4th Amendment UUD NRI 1945, also affected the composition of legislation to the existence of the MPR Tap which now only functions as beschikking. Therefore, it is necessary to find out to what extent the legitimacy of the Tap MPR as a statutory regulation is.